Impact of Agricultural Water Management Activities on Rural Poverty Alleviation with Reference to Gash Scheme, Sudan (2013) - Mohammed, Hysum Ibrahim; Mohamed, Ali Adeeb (Gezira Journal of Economic and Social Sciences, 2015)
Poverty alleviation is an essential issue for development process, and it considered as one of UN Millennium Development Goals (MDGs), there is worldwide agreement on the role of poverty alleviation as target of development policies and strategies, particularly for country like Sudan, which has high poverty incidence in rural and urban areas. This study aimed at investigating the impact of agricultural water management activities on alleviate rural poverty in Sudan: with reference to Gash scheme, Kassala State. The research depended on primary data collected by means of a questionnaire, which is distributed to a sample contained 240 respondents in the study area, half of them are members of Water User Associations (WUAs)  and the other half are not members (control group). Also  the study measured the level of  income and expenditure poverty  and the differences between means for some variables  among  the two groups of the study. The logistic regression model has  been adopted for predicting either some of the respondents can escape poverty line according to some basic  characteristics or not. The results suggested that the income and expenditure poverty indices have declined among the members of WUAs than non-members. The results revealed that there is significant differences between means of the two groups of study in favor of WUAs members, in term of household income, total revenues of the farm, household educational years and the total costs of the farming. The results of binary logistic regression model showed that households headed by member of water user associations are 3.8  times more likely to be above the poverty line than those headed by non members of theses associations and the household headed by literate persons are 1.3 more likely  have a chance to escape poverty line than those households headed by illiterate persons.